GUIDELINES FOR INTERNAL EDUCATIONAL QUALITY ASSURANCE ACCORDING TO THE 4 IDDHIPADAS PRINCIPLE OF PRIVATE SCHOOLS FOR ORDINARY EDUCATION IN NAKHON SI THAMMARAT PROVINCE - Bumroong-Ayosakoon, Thanunsich; Kosito, PhraPaladKosit; Somkhaoyai, Teeraphong; Chonrat, Veawtar (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were to study internal educational quality assurance according to the 4 iddhipadas principle, to compare internal educational quality assurance according to the 4 iddhipadas principle, and to present guidelines for internal educational quality assurance of private schools for ordinary education in Nakhon Si Thammarat province according to the 4 iddhipadas principle. This was a quantitative research using questionnaires, collecting data from 178 respondents. Additionally, using the interview form, data was collected from 5 key informants. Quantitative data was analyzed using percentage, standard deviation statistics, testing for t-test and content analysis. The research results show that: the implementation of internal educational quality assurance according to the 4 iddhipadas principle of private schools for ordinary education in Nakhon Si Thammarat province, was overall at a high level; the classification and comparison of the various aspects of internal educational quality assurance according to the 4 iddhipadas principle and their overall position, showed there were no statistically significant differences at a level of 0.05; most of the suggestions are aimed at school administrators. Lead the 4 iddhipadas principle applying them to PDCA cycle in all aspects of internal educational quality assurance.